Ross's Gulls in the Central Arctic Ocean - Hjort, Christian; Gudmundsson, Gudmundur A.; Elander, Magnus (ARCTIC, 1997)
The central Arctic Ocean is difficult to access, the result, the bird fauna of the area, with its potential input from all around the circumpolar perimeter, is still only little known. The present paper contributes observations on the distsribution of Ross's gull (Rhodosethia rosea) made during the Arctic Ocean 96 expedition from mid-July to mid-September 1996, from the Swedish icebreaker Oden. Ross's gull was the most common bird in the central parts of the Arctic Ocean, with a grand total at least 131 individuals seen up to 87 30 N. Its absence further north was judged as due to an early freeze-up. A marked concentration was noted at the shelf-break north of Franz Josef Land in late July. Most Ross's gulls were observed as single birds or two together, but some small flocks were seen, the largest consisting of 10 birds. Most birds were adults, the proportion of immature (second-year) birds being no more than 10-15%. Vu qu'il est difficile d'accéder à la partie centrale de l'océan Arctique, la faune aviaire de la région ainsi que l'apport à celle-ci venant de tout le périmètre circumpolaire sont relativement peu connus. Cet article présente des observations sur la distribution de la mouette rosée (Rhodostethia rosea) faites de la mi-juillet à la mi-septembre 1996 dans le cadre de l'expédition Océan Arctique 96 réalisée par le brise-glace suédois Oden. La mouette rosée était l'oiseau le plus répandu dans les régions centrales de l'océan Arctique, avec un total global d'au moins 131 individus observés jusqu'à 87° 30' de latit. N. On a interprété son absence plus au nord comme étant la conséquence d'un engel précoce. On a remarqué une forte concentration à la rupture de pente au nord de l'archipel François-Joseph à la fin juillet. La plupart des mouettes rosées ont été observées en solitaires ou en paires, mais on a aussi vu quelques petites volées dont la plus importante comptait 10 oiseaux. La plupart des mouettes étaient des adultes, la proportion des oiseaux immatures (dans leur deuxième année) ne ...